Pluralisme Pancasila - Arqom Kuswanjono (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 2006)
Pluralism is the term which it has many difference meaning. Atthe same time, someone can accept and refuse pluralism accordingto that meaning. Secular humanism argues that there is no anAbsolute Truth, because the truth is depend on human. The truth issubjective and relative, so unity just can be built by secularism.Global theology offers a new theology that is global theology tounite the difference religions. Syncretism selected and mixedreligions become a new religion. Perennial Philosophy tries to findmeeting is understood as a framework of interaction in whichgroups show point of religions in the esoteric area. In the socialsciences, pluralism sufficient respect and tolerance of each other,that they fruitfully coexist and interact without conflict or assimilation.Pluralism as theory is a social construction. Indonesian can constructpluralism base on the values of Pancasila that are Goddess,humanity, unity, democracy and justice.